Classifying Crohn's disease into colon-involving versus non-colon-involving groups is a better predictor of clinical outcomes than the Montreal classification. (December 2020) - Lin, Si-Nan; Zheng, Dan-Ping; Qiu, Yun; Zhang, Sheng-Hong; He, Yao; Chen, Bai-Li; Zeng, Zhi-Rong; Mao, Ren; Chen, Min-Hu
Background: A suitable disease classification is essential for individualized therapy in patients with Crohn's disease (CD). Although a potential mechanistic classification of colon-involving and non-colon-involving disease was suggested by recent genetic and microbiota studies, the clinical implication has seldom been investigated. We aimed to explore the association of this colonic-based classification with clinical outcomes in patients with CD compared with the Montreal classification. Methods: This was a retrospective study of CD patients from a tertiary referral center. Patients were categorized into colon-involving and non-colon-involving disease, and according to the Montreal classification. Clinico-demographic data, medications, and surgeries were compared between the two classifications. The primary outcome was the need for major abdominal surgery. Results: Of 934 patients, those with colonic involvement had an earlier median (interquartile range) age of onset [23.0 (17.0–30.0) versus 26.0 (19.0–35.0) years, p  = 0.001], higher frequency of perianal lesions (31.2% versus 14.5%, p  < 0.001) and extraintestinal manifestations (21.8% versus 14.5%, p  = 0.010), but lower frequency of stricture (B2) (16.3% versus 24.0%, p  = 0.005), than those with non-colon-involving disease. Colon-involving disease was a protective factor against major abdominal surgery [hazard ratio, 0.689; 95% confidence interval (CI), 0.481–0.985; p  = 0.041]. However, patients with colon-involving CD were more prone to steroids [odds ratio (OR), 1.793; 95% CI, 1.206–2.666; p  = 0.004] and azathioprine/6-mercaptopurine (AZA/6-MP) treatment (OR, 1.732; 95% CI, 1.103–2.719; p  = 0.017) than were patients with non-colon-involving disease. The Montreal classification was not predictive of surgery or steroids and AZA/6-MP treatment. Conclusion: This study supports the rationale for disease classification based on the involvement of colon. This new classification of CD is a better predictor of clinical outcomes than the Montreal classification.